Favorable course of previously undiagnosed Methylmalonic Aciduria with Homocystinuria (cblC type) presenting with pulmonary hypertension and aHUS in a young child: a case report - Luciano De Simone; Laura Capirchio; Rosa Maria Roperto; Paola Romagnani; Michele Sacchini; Maria Alice Donati; Maurizio de Martino (BMC, 2018)
Abstract Background Cobalamin C (cblC) defect is the most common inborn error of Vitamin B12 metabolism often causing severe neurological, renal, gastrointestinal and hematological symptoms. Onset with pulmonary hypertension (PAH) and atypical hemolytic-uremic syndrome (aHUS) is rare. Case presentation We describe the case of a 2-years old child, previously in good health, admitted to the hospital with severe respiratory symptoms, rapid worsening of clinical conditions, O2 desaturation and palmo-plantar edema. The patient showed PAH and laboratory findings compatible with aHUS. cblC defect, an inborn error of metabolism, was identified as the cause of all the symptoms described (cardiac, respiratory and renal involvement). Results of neonatal screening for inborn errors of metabolism had been negative. Administration of IM OHCbl (intramuscular hydroxocobalamin), oral betaine and symptomatic treatment with diuretics and anti-hypertensive systemic and pulmonary drugs induced dramatic improvement of both cardiac and systemic symptoms. Conclusions In this case of cblC defect the metabolic treatment completely reverted symptoms of aHUS and PAH. The course was favorable, and the prognosis is what we foresee for the future.